Evaluating the Performance of Different Types of Schemes of Selected Mutual Funds in India on the basis of Different Measures of Risk and Risk-adjusted Rate of Return during the time of Revival of the Economy in the recent past - Solanki, Prof. (Dr.) Umesh (IJRDO - Journal of Business Management, 2016)
This research work has considered the different schemes, classified into 4 categories, of 7 selected Mutual Funds of India. This research work was undertaken for the study and analysis of the performance of different types of schemes of selected Mutual Funds in India on the basis of their risk and risk-adjusted rate of return during the time of recent past recovery of the market from recession. If they were performing well even at that time then there are good prospects of growth. Because Mutual funds are one of the best investment avenues, even for the laymen, and hence, this research would be beneficial for all the investors to guide them to invest in the best available Mutual Funds schemes with lots of growth propositions and why? In the last, this research finds out many facts and figures about the major classes of Mutual Funds Schemes. On these facts and figures we conclude that Liquid and Money Market Mutual Funds Schemes are best one for investment because either they are providing best return or bearing least risk or both.